Therapeutic potential of Cervi Cornus Colla in zebrafish bone injury: implications for aquaculture - Fengxia Xu; Limin Dong; Limin Dong; Chengxue Qin; Yanru Ren; Liang Kong; Mengru Zhang; Haitao Du; Qing Xia; Cheng Wang; Ping Wang; Ping Wang (Frontiers in Marine Science)
IntroductionBone, as both a crucial organ with mechanical support and immune regulatory functions, profoundly influencing the growth and development of fish in aquaculture systems. Deer antler and its aqueous extract Cervi Cornus Colla (CCC), are natural medicinal substances known for their bone-protective properties.MethodsThis study investigated the osteoprotective effects of CCC against lipopolysaccharide (LPS)-induced injury to fish bones. An LPS-mediated zebrafish skeletal injury model was established and evaluated using Alcian Blue/Alizarin Red staining, fluorescence tracing, ELISA, and qPCR.ResultsThe median lethal concentration (LC50) of CCC in zebrafish was 206.3 mg/mL, and staining revealed that CCC reversed LPS-induced reduction in cartilage and bone formation in a dose-dependent manner. In Tg (mpeg1: EGFP) zebrafish, CCC treatment significantly decreased macrophages-associated green fluorescence, suggesting that the extract suppressed the activation of macrophages caused by LPS. CCC also reduced the production of several inflammatory factors (IL-6, IL- 1β, and NO). Furthermore, qRT-PCR confirmed CCC restored COL2α1 and Sox9a mRNA levels. Additional studies revealed CCC inhibits LPS-induced activation of the TGF-β/Smad3 signaling pathway.DiscussionThis study demonstrates that CCC can alleviate zebrafish bone injury, thereby providing an experimental basis for its application in the prevention and treatment of bone diseases in farmed fish.